Ante Natal Screening of Hyperglycemia: Situation analysis in Bangladesh - Sultana, Mst Tajmira; Hossain, Dina Layla; Mahmud, Sanzida; Parveen, Tabassum; Akter, Nahreen (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Hyperglycemia in pregnancy or Diabetic disorder is a state of glucose intolerance during pregnancy, carrying various adverse outcomes for mother and fetus. As it is a common disorder and appropriate measures can completely nullify its adverse effects so various international organizations formulated screening and management protocols. Bangladesh is a South Asian country with high predisposition of this disease, so universal screening in first contact with pregnant woman by appropriate protocol along with precise interpretation and interventions are desirable. But we found that obstetricians and some other physicians sometimes remain reluctant on this task. Report shows that 44.4% of physicians prefer blood sugar screening at 1 st antenatal care and only 16.3% advice IADPSG, WHO and ACOG standard 3 samples OGTT for screening. More than 80% use HbA1c for blood sugar monitoring and 40% use it for diagnosis of glucose intolerance which is an unreliable method, specially during pregnancy and adverse outcomes remain unprotected for a large number of patient. So, we should find out our pitfalls in this regard for a healthy nation at present and future. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(1): 41-45